STUDENTS’ PROBLEM ENCOUNTERED DURING LISTENING ACTIVITIES IN STKIP AL MAKSUM LANGKAT - ROSMEN; Edi Suprayetno; Ratih (LPPM STKIP AL MAKSUM, 2022)
This study investigated students’ problem encountered during listeningactivities in STKIP Al Maksum Langkat. The subjects wereeighty-three students of the first semester of English Department StudyProgram. Basic qualitative studies suggest by Ary adopted in thisstudy. Questionaries and interview administered in order to collect thedata. The data informed that there were difficulties faced by thestudents in the listening activities, they were the speakers’ speed, theaccent of the speaker, unknown words, and difficulties in recognizingmain points. It was expected that enhancing students’ motivation topractice listening with authentic materials and in every learningactivities administering authentic materials deemed necessary in orderto insincere a real situation of native talks and conversation tounderstand the culture and points in their talks. Acquiring amounts ofvocabularies expected enhanced by the students in order to ease thelistening activities.